Transcriptome profile analysis in spinal cord injury rats with transplantation of menstrual blood-derived stem cells - Qi, Longju; Jiang, Wenwei; He, Wenhua; Li, Xiangzhe; Wu, Jiahuan; Chen, Shiyuan; Liao, Zehua; Yu, Shumin; Liu, Jinyi; Sun, Yuyu; Wu, Qinfeng; Dong, Chuanming; et al. (Frontiers in Molecular Neuroscience, 2024)
Menstrual blood-derived stem cells (MenSCs) are vital in treating many degenerative and traumatic disorders. However, the underlying molecular mechanisms remain obscure in MenSCs-treating spinal cord injury (SCI) rats. Here, MenSCs were adopted into the injured sites of rat spinal cords at day 7 post surgery and the tissues were harvested for total RNA sequencing analysis at day 21 after surgery to investigate the expression patterns of RNAs. A total of 89 lncRNAs, 65 circRNAs, 120 miRNAs and 422 mRNAs were significantly upregulated and 65 lncRNAs, 72 circRNAs, 74 miRNAs, and 190 mRNAs were significantly downregulated in the MenSCs treated rats compared to SCI ones. Next, expression of selected miRNAs, lncRNAs, circRNAs and mRNAs were validated by quantitative realtime polymerase chain reaction (qRT-PCR). Bioinformatics packages and extra databases were enrolled to scoop the genes functions and their interaction relationships. Current investigation revealed that MenSCs treatment improve the recovery of the injured rats and the most significantly involved pathways in SCI regeneration were cell adhesion molecules, nature killer cell mediated cytotoxicity, primary immunodeficiency, chemokine signaling pathway, T cell receptor signaling pathway and B cell receptor signaling pathway. Moreover, the lncRNA-miRNA-mRNA and circRNA-miRNA-mRNA competitive endogenous RNAs (ceRNA) network of SCI was constructed. Finally, proteins interaction loops were checked by protein-protein interaction (PPI) network. In summary, the above results revealed the expression profile and potential functions of differentially expressed (DE) RNAs in the injured spinal cords of rats in the MenSCs-treated and SCI groups, and this study may provide new clues to understand the mechanisms of MenSCs in treating SCI.